2016
DOI: 10.4028/www.scientific.net/kem.717.47
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Reinforcement of ZDMA in EPDM

Abstract: We researched the reinforcement effect of commercial Zinc methacrylate (ZDMA) on ethylene propylene diene monomer (EPDM), ZDMA was added to EPDM directly with hakke internal mixer. The mechanical properties, SEM, RPA and FTIR were synthetically used to study the reinforcement effect, compared with the reinforcement of CB N330. The results showed that the reinforcement effect of ZDMA on EPDM was better than that of CB N330. The tensile strength of vulcanizate with ZDMA was up to 17MPa, and the elongation at bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Figure 2a,b show the FTIR spectra of the HNBR/ZDMA and HNBR/ZDMA‐8MMBZ composites heated at 170°C for different times. The characteristic peak at 943 cm −1 was attributed to the out‐of‐plane bending vibration CH of H 2 CC, 34 and the intensity decreased with increasing heating time. This was because ZDMA gradually polymerized to form PZDMA under peroxide initiation, which weakened the CH absorption peak in H 2 CC.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2a,b show the FTIR spectra of the HNBR/ZDMA and HNBR/ZDMA‐8MMBZ composites heated at 170°C for different times. The characteristic peak at 943 cm −1 was attributed to the out‐of‐plane bending vibration CH of H 2 CC, 34 and the intensity decreased with increasing heating time. This was because ZDMA gradually polymerized to form PZDMA under peroxide initiation, which weakened the CH absorption peak in H 2 CC.…”
Section: Resultsmentioning
confidence: 99%
“…6 Metal salts of unsaturated carboxylic acids have been found to act as effective reinforcing additives for elastomers. [7][8][9][10][11][12][13][14][15][16][17][18] It was found that compared with other conventional reinforcing filler such as carbon black or silica, 19,20 the excellent mechanical properties of the vulcanizates can be obtained with the incorporation of zinc dimethacrylate (ZDMA). Via a procession of vulcanization, the ZDMA can be polymerized by using peroxide as curing agent; moreover, homo-and graft-polymerization could take place.…”
Section: Introductionmentioning
confidence: 99%